(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article says that the beginning of bilingual literary creativity in our native language began with folk literature, and the process of its formation and development was established primarily thanks to mutual traditions, rituals, and creative connections of fraternal peoples. It is noted that the linguistic, literary and other closeness of related peoples, in turn, contributed to the emergence of bilingual creativity between the two peoples. It is clear that the ancient written monuments found throughout the vast territory of Asia were written by various Turkic tribes, and most of them belong to the Kyrgyz. It is also emphasized that during the period of professional written literature of the Kyrgyz people of the 20-30s of the twentieth century, it was mainly formed through a bilingual creative process.